Thrust Analysis of the RX-70 Rocket Using Burnsim Simulation with Variations in RDX Content and Grain Geometry - Adzan, Muhammad Ichsanul; Ruyat, Yayat; Wibowo, Heri Budi (Jurnal Pijar Mipa, 2025)
Indonesia, as the largest archipelagic country in the world with a strategic geographical position, has an urgent need to develop a reliable defence system, one of which is through rocket technology. The RX-70 rocket is one of the national rocket development programs designed to strengthen domestic defence capabilities. This study aims to analyze the thrust performance of the RX-70 rocket motor with a numerical simulation approach using BurnSim software. The main focus of this study is to evaluate the effect of variations in Cyclotrimethylenetrinitramine (RDX) content and star grain geometry configuration on the combustion characteristics and thrust performance of a rocket based on composite propellant containing Ammonium Perchlorate (AP), Aluminium (Al), and HTPB binder. The study was conducted quantitatively using simulations based on optimized propellant formulation data using ProPEP software. Variations in the number of star grains analyzed included configurations of 3 to 9 star points, with RDX content varying from 0% to 20% by weight. The simulation results showed that increasing the number of star grains contributed significantly to increasing the combustion surface area, which had a direct impact on increasing maximum thrust and reducing burn time. This shows that grain geometry has a dominant influence on motor performance compared to variations in RDX content in the tested range. On the other hand, the addition of RDX did not significantly increase thrust, but had an impact on combustion efficiency and the formation of condensed combustion products (CCPs). Higher RDX content tends to produce greater agglomeration of aluminium particles, which has an impact on decreasing combustion efficiency. The Star 8 configuration with the fifth variation showed the best performance, with the highest combustion chamber pressure reaching 753 psi and a stable thrust above 2,090 N. These findings emphasize the importance of grain geometry optimization in rocket motor design, as well as the need for a balance between energetic material content and combustion efficiency. This research contributes to the development of composite propellant design for national defence applications. To strengthen the validity of the findings, full-scale experimental testing is recommended to compare simulation results with actual performance in the field.